Social Responsibility at King Saud University and Its Relationship with Academic Satisfaction from the Perspective of Graduate Students - Al-Maatash, Ibrahim Nasser Saud (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the nature of the relationship between social responsibility at King Saud University and academic satisfaction from the perspective of postgraduate students. The research adopted a descriptive correlational approach and employed a questionnaire administered to a stratified random sample consisting of 480 postgraduate students. The findings revealed that the level of social responsibility at King Saud University had a mean score of 3.76 out of 5, while academic satisfaction had a mean of 3.79 out of 5, with both rated at a high level according to the adopted evaluation criterion. The results also indicated a statistically significant and positive correlation between overall university social responsibility and overall academic satisfaction at the level of (r = 0.81, α ≤ 0.01), reflecting a strong relationship between the two variables. Additionally, the study uncovered statistically significant differences in the perception of social responsibility attributable to the gender variable in favor of female students; differences in academic satisfaction attributable to the nationality variable in favor of Saudi students; and differences in both variables attributable to the educational level in favor of doctoral students. Based on these findings, the researcher recommends enhancing awareness of the various dimensions of university social responsibility, particularly in regard to environmental sustainability, which received the lowest mean score among the measured dimensions and developing community-based initiatives. The study also suggests conducting further research.
Keywords: University social responsibility; academic satisfaction; postgraduate students; King Saud University